A Grounded Theory of Master's‐Level Counselor Research Identity. (March 2015) - Jorgensen, Maribeth F.; Duncan, Kelly
<x xml:space="preserve">Abstract</x> A grounded theory approach was used to examine the research identity of 17 master's‐level counseling trainees and practitioners. The emergent theory gave an understanding to sources of variation in the process and outcome of research identity. The authors provide recommendations for counselor educators to use with current and former students.